Projekt języka ogólnoświatowego („Linguaz Universale”) Rasmusa Kristiana Raska - Sakaguchi, Alicja (Scripta Neophilologica Posnaniensia, 2018)
Projekt języka ogólnoświatowego („Linguaz Universale”) Rasmusa Kristiana Raska